Integrative DNA methylome and transcriptome analysis illuminate leaf phenotype alterations in tetraploid citrus - Hu Gao; Gong-Ao Xiao; Yi Bao; Qiang-Ming Xia; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Horticulture Advances)
Abstract Whole-genome duplication (WGD) in plants triggers profound morphological and physiological changes, with DNA modification being a key epigenetic factor that helps neo-polyploids overcome challenges and gain adaptive advantages. Tetraploids were previously mined from diploid citrus seedlings, showing enhanced environmental adaptability and potential as rootstocks. These tetraploids exhibited increased leaf and cell wall thickness compared to their diploid counterparts. To explore the impact of WGD, transcriptomic and whole-genome bisulfite sequencing (WGBS) were conducted on two pairs of citrus tetraploids and their diploid controls, revealing significant molecular changes. Notably, tetraploid citrus displayed lower CG methylation levels in gene and transposable element (TE) bodies relative to diploids. Differentially methylated genes (DMGs) between tetraploids and diploids were primarily associated with immune stress, organ development, metabolic pathways, and secondary metabolism. In Trifoliate orange (Poncirus trifoliata L. Raf.) and Ziyang Xiangcheng (Citrus junos Sieb. ex Tanaka), only 150 and 58 differentially expressed genes (DEGs) were identified, respectively, with enrichment in critical cellular processes such as cell wall synthesis, plastid development, and pathways modulating chloroplasts and plasma membranes. A total of 70 genes showed both differential methylation and expression, including ACN1, Nac036, and ASMT1, which are involved in stomatal development, leaf morphology, and melatonin synthesis, respectively, offering insight into the regulatory mechanisms of phenotype alterations after polyploidization. These findings reveal the epigenetic modifications in polyploid citrus and highlight the role of polyploidization-induced methylation in driving phenotypic changes.